Néhány gondolat a szoftverek szabadalmazhatóságáról - Petkó, Mihály (Debreceni Jogi Műhely, 2008)
I’m presenting in my study the Hungarian software’s legal system. The Hungarian law system is protecting the software in the copyright law, like a literary property. This resolution given more latitude for the author, but it has many problems of the evidence, because not registred the property – like the patent – cause the author’s being can prove difficultly. In the patent law has not problem with the evidence thanks for the state register, but the legal process longer and costly more money. Primarily the Hungarian patent law is protecting the industrial, technical property. The software not an exclusively industrial, technical produce, there is closer the literary property about the author’s intellectual work. The protection of the Hungarian copyright is cheaper and faster than the protection in the area of patent law, and it covers more contract liberty for the partners. The Hungarian civil law is based upon the monist conception in the field of intellectual property. This means that pecuniary and personality rights are indivisible. In spite of this competition on the market prefers contracts that ensure exclusive, unambiguous rights. This area of law claims contracts suit to these conditions. The personal rights in the Hungarian copyright are remaining for the author, also the pecuniary rights. But - thanks for the successful software’s lobby - in this question the regulation diverged: the pecuniary rights may be transferring for the users, costumers. This regulation is better (cheaper, an easier) for the buyers under the Hungarian regulations of patent law. In Hungary a lot of software contract was established under the British legal system. The Hungarian legal culture accepted and using these contract forms. The Hungarian regulation concerning to the software questions is dualist like the British one. The pecuniary rights can be transferred free, just the personality rights belong to the author. The users can buy the rights need for using and it gives enough defense as a shield. The author’s interests are not sweating because of the personality rights stay under his domain. In my opinion the question is whether the Hungarian legal defense equally serves the author’s and the users’ interests. The process in patent law is longer, needs more money for supporting the protection and there are some conceptual problems between the software and the patent ideas. The new regulation is not reasonable.